Analisis Pemeriksaan Lumbal Pada Kasus Low Back Pain (LBP) Di Instalasi Radiologi RSUD Kota Bogor - Sumantri Sebayang; Kadek Yuda Astina; Triningsih Triningsih; I Kadek Sukadana; Nova Adeline (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
The aim of this research is to determine the Lumbar MRI examination procedure in LBP cases at the Bogor City Regional Hospital, namely STIR and Myelo Radial, the aim of which is to clearly see abnor malities in the intervertebral discs and stenosis in the cerebral spinal cord. This type of research uses descriptive qualitative methods with a case study approach. Data collection methods are carried out through observation, interviews and documentation. Then data analysis was carried out using open coding charts, so that conclusions could be drawn. The results of this study show that the Lumbar MRI examination procedure in cases of Low Back Pain (LBP) at the Bogor City Regional Hospital does not require special preparation, the patient comes to radiology for screening (installation of a pacemaker). The patient removes clothing and metal objects. Before the examination, the patient is asked to urinate first, the patient's position is supine (feet first), iso center 5 cm superior to the ASIS. Then it is briefly explained that during the examination you are not allowed to move and the duration of the examination is 15 minutes and the role of the sagittal STIR sequence and Myelo Radial. The role of the sagittal STIR sequence and myelo radial to suppress fat in the cerebral spinal fluid, conus medullaris and myelum in the spinal cord and to see masses Lesions and stenosis caused by narrowing of the bulging in the intervertebral disks are clear enough to provide a Lumbar MRI image for cases of Low Back Pain (LBP).